DIGITALISASI EMAS DALAM PERSPEKTIF SYARIAH: STUDI PADA EKOSISTEM BULLION BANK INDONESIA - Masrur, Ahmad Rajaul Masrur; Holis, Moh; Musoffan (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the implementation of gold digitalization within the Bullion Bank ecosystem from a sharia perspective. The research is motivated by the rapid advancement of financial technology and the rising public interest in digital gold investment as a secure and sharia-compliant asset. Using a qualitative descriptive approach with a case study method, data were collected through interviews, document analysis, and literature review. The findings reveal that Bullion Bank integrates blockchain technology, sharia-compliant contracts (akad), and physical gold custodianship to ensure transparency and asset-backing (tangible underlying). The system complies with key sharia principles, such as avoiding riba (interest) and gharar (uncertainty), and ensuring qabdh hukmi (legal possession). Moreover, the application of smart contracts within blockchain technology strengthens transaction validity and ownership records in accordance with Islamic law. However, challenges remain in harmonizing regulations, conducting periodic sharia audits, and improving consumer literacy regarding digital gold ownership. The study contributes to the academic discourse on Islamic fintech by demonstrating how modern financial innovation can align with fiqh muamalah. It also offers strategic insights for regulators and industry stakeholders to develop sustainable, transparent, and sharia-compliant digital gold ecosystems in Indonesia. Keywords: digital gold, sharia, Bullion Bank, blockchain, Islamic fintech